Courses
Courses for Kids
Free study material
Offline Centres
More
Store Icon
Store

Solve the equation given below:
$\dfrac{3}{4}(x - 1) = x - 3$

seo-qna
Last updated date: 28th May 2024
Total views: 435.6k
Views today: 11.35k
Answer
VerifiedVerified
435.6k+ views
Hint: The given equation is a degree one polynomial equation. The solution of these equations is given by using simple arithmetic operations.

Given equation is
$ \Rightarrow \dfrac{3}{4}(x - 1) = x - 3$
Multiplying both sides of the equation by 4, we get
$
   \Rightarrow 4 \times \dfrac{3}{4}(x - 1) = 4 \times (x - 3) \\
   \Rightarrow 3(x - 1) = 4(x - 3) \\
 $
Solving the above equation for the value of x, we get
$
   \Rightarrow 3x - 3 = 4x - 12 \\
   \Rightarrow 4x - 3x = 12 - 3 \\
   \Rightarrow x = 9 \\
 $
Hence the value of x is $9$ .

Note: Polynomial equations of degree one can be easily solved by simple arithmetic operations while polynomials of degree greater than one are little bit difficult to solve. To solve polynomials of degree greater than one arithmetic operations and factorization methods are required. By factorising we break the higher degree polynomial in multiples of lower degree polynomial.